Race Against Antimicrobial Resistance Requires Coordinated Action – An Overview - Premanandh, J.; Samara, B. S.; Mazen, A. N. (Frontiers in Microbiology, 2016)
Resistance developed by microbes is challenging success stories of treatment of infectious diseases with anti-microbials. Developing new antimicrobials against these resistant organisms does not progress at the same speed. In an effort to address this key issue, this work overviews the role of different stakeholders and discusses preventative and control measures for effective management of available resources. Roles and concerns of physicians, pharmacists and the public are also discussed. More than anything, this situation requires immediate action to establish antimicrobial stewardship program, control over the counter sale and promote public awareness. The paper also confronts the idea of curbing the use of antimicrobials using mass media, while detailing the consequences of non-therapeutic use. The role of policy makers in taking global action is essential to establishing authority or agency for formulating national guidelines and regulations for prudently using antimicrobials. To do this, this paper recommend the establishment of a global fund. In conclusion, the race against resistance is a collective responsibility requiring coordinated action at local, national, regional and international levels to ensure sustained utilization of antimicrobials.